Factors associated with the compliance of standard precaution; review article - Shah Zeb; Tazeen Saeed Ali (Journal of the Pakistan Medical Association, 2020)
Abstract Compliance with standard precautions is very important for healthcare workers because studies have shown that it helps in minimising the transmission of infectious diseases and healthcare-associated infections which is directly proportional to the patient cost and stay of the patient in hospitals. As healthcare associated infections increase, the cost and the stay of the patient will increase. Researchers suggest that all healthcare workers need to follow the standard precautions guideline and it can be possible with the help of health education, training, provision of equipment and supervision by the management. Barriers to the compliance identified are lack of education, heavy workload, unavailability of equipment, lack of resources and lack of access to supplies. The lack of education and heavy workload are the major factors faced by the nurses. Key Words: Healthcare workers, Universal precautions, Standard precautions